Steward's Fork : a sustainable future for the Klamath Mountains - Agee, James K. (University of California Press, 2007)
'Steward's Fork' explores northwest California's magnificent Klamath Mountains - a region that boasts remarkable biodiversity and a wealth of natural resources that have been used, and more recently abused, by humans for millennia.